Apuntes sobre el arbitraje en la nueva ley general de contrataciones públicas - Juárez Guerra, Luis (Pontificia Universidad Católica del Perú, 2025)
This article analyzes several arbitration provisions contained in the new General Law on Public Procurement – Law No. 32069, which, in the author’s view, are controversial, incomplete, or require further development for better understanding. In particular, it examines aspects related to procedural rules applicable to arbitration, substantive rules governing the merits of the case, judicialization of claims arising from the total or partial non-approval of additional services, continuity in the performance of contractual obligations, the statute of limitations in arbitration, the binding nature of the arbitral award, and the countersecurity required for interim measures.

Mediante el presente artículo se analizan algunas de las disposiciones arbitrales contenidas en la nueva Ley General de Contrataciones Públicas – Ley N.° 32069 que, a criterio del autor, resultan controvertidas, se presentan incompletas o merecen un mayor desarrollo para su mejor comprensión. En particular, se analizan aspectos vinculados a normas procesales aplicables al arbitraje, normas sustantivas aplicables al fondo del asunto, judicialización de pretensiones derivadas de la falta de aprobación total o parcial de prestaciones adicionales, continuidad de ejecución de prestaciones, la caducidad en el arbitraje, el carácter obligatorio del laudo arbitral y, la contracautela de medidas cautelares.
Notes on Arbitration in the New General Law on Public Procurement
Keywords: Arbitration; Public Procurement; Law; Regulation; Arbitraje; Contrataciones Públicas; Ley; Reglamento; https://purl.org/pe-repo/ocde/ford#5.05.00